EXPERIMENTAL DEFORMATION OF MUSCOVITE SHEAR ZONES AT HIGH TEMPERATURES UNDER HYDROTHERMAL CONDITIONS AND THE STRENGTH OF PHYLLOSILICATE-BEARING FAULTS IN NATURE - Mariani E.; Brodie K.H.; Rutter E.H. (My University, 2006)
Layers of fine-grained muscovite were hot-pressed then sheared between alumina sliders to shear strains up to 2, at temperatures between 300 and 700 °C, confining pressures of 206 MPa and various pore water pressures. High pore water pressures helped suppress dehydroxylation of the mica and permitted testing at temperatures higher than previously used. Shear strain rates between 10-3 s-1 and 10-7 s-1 were accessed using constant shear strain rate and stress relaxation testing. Except for strain rates <10-5 s-1 at 700 °C, deformation was strain rate and temperature-insensitive, but effective normal stress-sensitive with a friction coefficient at yield of 0.3, rising with strain to 0.5. Steady-state sliding was not attained. From the mechanical data and microstructural study, deformation was inferred to have occurred by a mixture of brittle/frictional and crystal plastic processes. At 700 °C and low strain rates the shear strength falls rapidly with a linear-viscous characteristic, in a way not previously reported. This is tentatively attributed to rate-control by viscous glide of basal dislocations. Extrapolating these results to geological strain rates, we expect mica-rich fault zones will exhibit frictional behaviour with a low friction coefficient between 0.25 and 0.5, giving way at mid-crustal conditions to a rapid strength drop as viscous creep supervenes. Thus mid- to lower-crustal, mica dominated faults of any orientation, and terrains of schistose, metapelitic rocks in the cores of orogeneic belts, are expected to be very weak, supporting shear stresses in the range 1-10 MPa. The frictional behaviour of mica-rich faults in upper-crustal regions is, however, expected to be too strong to account alone for the proposed weakness of some major fault zones. © 2006 Elsevier Ltd. All rights reserved.
Keywords: FRICTION COEFFICIENT; HIGH TEMPERATURE; PHYLLOSILICATE-RICH FAULT ZONES; POLYCRYSTALLINE MUSCOVITE; SIMULATED SHEAR ZONES; VISCOUS GLIDE OF DISLOCATIONS